Industrial material hot air drying device - ZHOU CONGBING (2017)
The invention discloses an industrial material hot air drying device. The industrial material hot air drying device comprises a main body; and the main body includes feed ports and a variable frequency motor. Multiple feed ports are formed in the side wall of the main body; a fan is arranged above the main body; an airflow equal-dividing plate is arranged at the top end in the main body; a base is arranged below the main body; the variable frequency motor is arranged between the base and the main body; an output part of the variable frequency motor is connected with a stirring shaft; and multiple baffle plates are arranged in the main body. The industrial material hot air drying device has such advantages as reasonable structure design, good drying effect and convenience for use. 本发明公开了种工业物料热风干燥装置，它包括本体，所述本体包括进料口和变频电机。所述本体侧壁设置有多个进料口；所述本体上方设置有风机；所述本体内部顶端位置设置有气流均分板；所述本体下方设置有底座；所述底座和本体之间设置有变频电机；所述变频电机的输出部分连接有搅拌轴；所述本体内部设置有多个折流板。本发明具有结构设计合理、干燥效果好和使用方便等优点。